A study on the employment and wage outcomes of persons living with a same-sex partner - Lena Hassani-Nezhad; Sevane Ananian; Nick Drydakis (International Labour Organization (ILO), 2024)
This study examines the labour market disparities faced by same-sex couples across nine countries (Argentina, Brazil, Chile, Colombia, France, Mexico, Thailand, the United States of America and the Bolivarian Republic of Venezuela), extending the focus of previous studies by looking beyond developed countries. Consistent with the existing literature, the findings presented here show that, in many countries, men in same-sex couples participate in the labour market to a lesser extent, experience higher unemployment rates and receive lower wages than comparable men in opposite-sex couples. Conversely, women in same-sex couples are more likely to be employed than comparable heterosexual women and to enjoy a wage premium in some countries. Finally, it makes the case for further research, especially in developing countries.
Keywords: 330